A simple and effective enrichment process of the antiproliferative lignan arctigenin based on the endogenous enzymatic hydrolysis of Serratula tinctoria and Arctium lappa fruits. Issue 12 (December 2015) - Sólyomváry, Anna; Mervai, Zsolt; Tóth, Gergő; Ress, Ágnes Evelin; Noszál, Béla; Molnár-Perl, Ibolya; Baghy, Kornélia; Kovalszky, Ilona; Boldizsár, Imre
Graphical abstract: Highlights: A simple, effective method was developed to prepare the precious lignan arctigenin. Method was based on the enzymatic hydrolysis of S. tinctoria and A. lappa fruits. Enzyme-hydrolyzed fruit of S. tinctoria is a new and rich source of arctigenin. Arctigenin was proved to inhibit the microtubular system of SW480 carcinoma cells. Abstract: A simple, effective and environmentally friendly method was developed to prepare the precious lignan arctigenin, in as high as 88.1% and 85.2% purity, from the fruits of Serratula tinctoria and Arctium lappa . In the course of this study, arctiin, the glycoside of arctigenin already known in A. lappa, was determined as the main compound in S. tinctoria fruit for the first time. In both samples, hydrophilic arctiin was converted into its hydrophobic aglycone arctigenin by endogenous enzymatic hydrolysis, allowing the preparation of high-purity arctigenin extract (HPAE) by an optimized three-step process. Firstly, fruits were purified with diethyl ether to remove all of their hydrophobic constituents. Thereafter, the arctiin remaining in the fruits was converted into arctigenin in aqueous medium by enzyme treatment. Finally, formed arctigenin was extracted with diethyl ether to prepare HPAE. Thus, 11.3 mg and 10.1 mg HPAE containing 9.96 mg and 8.61 mg arctigenin was isolated from 200.0 mg S. tinctoria and A. lappa fruits respectively, using only 16 mL ether and 0.5 mL water. The applicability of the method to a large-scale HPAE isolation was also confirmed. Arctigenin and its structurally related compound trachelogenin were proved to significantly inhibit the microtubular system of SW480 adenocarcinoma cells.